2018
DOI: 10.1039/c8cc03136c
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunctions of silver–iron oxide on graphene for laser-coupled oxygen reduction reactions

Abstract: We report a two-step hybridization of N-doped graphene and Ag-decorated Fe2O3 hematite to realize a balanced oxygen adsorption/desorption equilibrium and a laser-coupled ORR (LORR). The stable plateau currents with n values of 3.9 in a wide potential range (0.2-0.7 V) and 7.5% peroxide inhibition of the LORR are found to be directly associated with the Ag/Fe2O3 heterojunction, where interactions of semiconductor band gap excitation and plasmonic resonance-induced hot electrons are proposed to occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…For further explorations, theoretical simulation about the interactions between the intermediates and the catalytic surface for thermodynamics and molecular dynamics could be an important approach for in‐depth understanding. Due to the intrinsic correlation between redox of H 2 O 2 and oxygen reduction reaction, the electrocatalyst with a low overpotential for ORR might be favorable for H 2 O 2 redox . It is worth noting that, most recent free‐standing 3D electrodes are tested in the typical three‐electrode system, real self‐standing devices integrating 3D electrodes with suitable reference electrode and counter electrode are in need for practical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For further explorations, theoretical simulation about the interactions between the intermediates and the catalytic surface for thermodynamics and molecular dynamics could be an important approach for in‐depth understanding. Due to the intrinsic correlation between redox of H 2 O 2 and oxygen reduction reaction, the electrocatalyst with a low overpotential for ORR might be favorable for H 2 O 2 redox . It is worth noting that, most recent free‐standing 3D electrodes are tested in the typical three‐electrode system, real self‐standing devices integrating 3D electrodes with suitable reference electrode and counter electrode are in need for practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the intrinsic correlation between redox of H 2 O 2 and oxygen reduction reaction, the electrocatalyst with a low overpotential for ORR might be favorable for H 2 O 2 redox. [175,176] It is worth noting that, most recent free- [170] Reprinted with permission from [170], copyright 2014, with permission from Elsevier. (c) Structure of Au-luminol based microelectrode for electrochemical imaging of intracellular H 2 O 2 ; (d) image of the microelectrode in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Diverse shapes of nanoparticles distributed and anchored on graphene sheets can be achieved by varying synthesis conditions. 33,34 Additionally, conductive polymers such as polyaniline (PANI) have also been used to functionalize MoS 2 to improve the electro conductivity of the materials for the detection of dopamine. 35 MoS 2 /PANI/rGO aerogel nanocomposite exhibited excellent long-term cycling stability and a high capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocatalytic results indicated that the metal‐free catalyst could also show excellent catalytic performances for ORR. From then on, nitrogen‐doped carbon nanotubes, nitrogen‐doped graphene, C 3 N 4 , and other carbon‐based materials became the research focus in the field of electrocatalysis . Besides N atoms, other non‐metal atoms such as S, B, and P as well as the transition metal atoms such as Fe, Co, Ni, and Cu have been chosen as the heteroatoms in carbon materials to form doped catalysts for ORR .…”
Section: Introductionmentioning
confidence: 99%
“…From then on, nitrogen-doped carbon nanotubes, nitrogen-doped graphene, C 3 N 4 , and other carbon-based materials became the research focus in the field of electrocatalysis. [17][18][19][20][21][22][23][24] Besides N atoms, other non-metal atoms such as S, B, and P as well as the transition metal atoms such as Fe, Co, Ni, and Cu have been chosen as the heteroatoms in carbon materials to form doped catalysts for ORR. [25][26][27][28][29][30] It is reported that the high catalytic activity and stability of the catalysts pyrolyzed at high temperature arise from the active sites such as Fe, FeN x , FeO x , and FeC, which makes the heteroatom-doped carbon materials have comparable catalytic performances with Pt-based catalysts.…”
Section: Introductionmentioning
confidence: 99%